ANALISIS PENGARUH KEPEMIMPINAN VISIONER, BUDAYA ORGANISASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PUNDI MAS BERJAYA MEDAN - Sahat Simbolon (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2020)
The study aims to describe the effecf of visionary leadership, organizational behavior, and work environtment on employee work performance at PT. Pundi Mas Berjaya Medan. This research was conducted for 5 (five) months, start from May 2019 to September 2019. This research use non probability sampling method. The respondents of this research are all employee at PT. Pundi Mas Berjaya Medan which amounted to 72 (seventy two) employees. The instrument is used a questionnaire to collect data from visionary leadership variable, organizational behavior variabel, work environtment variable, and work performance variable. Data analysis technique used is validity test, reliability test, descriptive analysis, multicolinearity test, normality test, multiple linear regression analysis, multiple linear correlation coefficient test, partial hypothesis test ot t test, simultaneous hypothesis test or F test, and calculation of coefficient of determination. The result of descriptive analysis visionary leadership variable, organizational behavior variabel, work environtment variable, and work performance variable are in good category at PT. Pundi Mas Berjaya Medan. Based on partial analysis, visionary leadership, organizational behavior and work environtment have a positive and significant effect on employee work peformance at PT. Pundi Mas Berjaya Medan. Simultaneously, visionary leadership, organizational behavior, and work environment have a positive and significant influence on employee work performance at PT. Pundi Mas Berjaya Medan. The contribution of visionary leadership, organizational behavior and work environtment variable to improve the employee work performance variable is 0,822 or 82,2 %, while rest of 0,178 or 17,8% influenced by other variable not examined by writer in this research, such as work discipline, motivation, and work satisfaction. Keywords : visionary leadership, organizational behavior, work environment, work performance